The Influence of Leadership and Communication on Motivation and Performance of Educational Authority Employees Nagekeo Municipality - Menge, Irmgardis Wea; Edy Mulyono, Sungkowo; Sukirman, Sukirman (Educational Management, 2021)
Poor employee performance needs further investigation. Ideally, employees that perform optimally indicate their qualified self-identities. This research aims to find out, explain, and analyze the leadership of the head of service and communication toward motivation and performance of educational authority employees in Nagekeo municipality, NTT. This research is quantitative research with Path Analysis.The quantitative approach allows this research to investigate the causalities of several influential factors toward employees' performances. The population of this research consisted of forty educational authority employees in Nagekeo municipality. The data were collected through questionnaire and documentary study. Then, the data would be validated to check their reliability. The applied data analysis technique was hypothesis test assisted by SPSS. Then, the data were analyzed by Path Analysis and assisted by SPSS. The findings showed that the head of the agency, communication, and motivation influenced directly to the employees' performances. Leadership and communication, moderated by motivation, did not directly influence the performance. Therefore, this research recommends that: (1) the head of service and communication, with all his authorities, could improve his supervision toward the employees, (2) the employees should optimally perform for the sake of better educational advancement in Nagekeo. Keywords: The leadership of the agency head, Communication, Motivation, Performance